Additive manufacturing method for generating nanoparticle strengthening phase through in-situ reaction of aluminum-silicon alloy
By introducing the reactive gas in situ to generate nanoparticle reinforced phases in the selected laser melting additive manufacturing, the problem of low strength of the formed parts in the selected laser melting technology is solved, and the high-efficiency mechanical properties and density of aluminum-silicon alloys are improved.
Patent Information
- Application Number
- CN202411405195.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The strength of the selected laser melting technology is low. The existing methods such as the addition of magnesium elements or the enhancement of micron phases is limited, and there are problems of decreasing toughness and plasticity, making it difficult to effectively refine the structure of the aluminum-silicon alloy during solidification.
Reactive gases, such as N2 and C2H2, are introduced in the selected laser melting additive manufacturing process, and the chemical reaction between the laser melting powder and the gas is used to generate nanoparticle reinforced phases in situ to achieve uniform distribution within the material.
The nano-reinforced phase generated in situ significantly improves the mechanical strength and density of aluminum-silicon alloys, maintains good toughness, is suitable for mass production and reduces grain size.
Smart Images

Figure CN119282141A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high-performance alloy preparation in a selective laser melting additive manufacturing process, and in particular to an additive manufacturing method for generating a nanoparticle reinforcement phase by in-situ reaction of an aluminum-silicon alloy. Background Art
[0002] Selective laser melting technology is an additive manufacturing technology that uses laser as a high-energy heat source to selectively melt metal powder from bottom to top, point by point, line by line, and layer by layer based on a three-dimensional slice model of metal parts, ultimately achieving mold-free, fully dense, and near-net-shape metal complex components. Compared with traditional subtractive manufacturing technology, this technology is characterized by high forming flexibility, great time and cost savings, and is suitable for manufacturing metal parts with complex structures. It can effectively reduce the number of welds and parts in traditional manufacturing processes. It can achieve high reliability, intensive and lightweight manufacturing, especially suitable for precise and rapid manufacturing of complex structural parts. It is a rapid prototyping technology with great development prospects. Although laser selective melting technology has many of the above advantages, its formed parts still have shortcomings, such as low strength of formed parts.
[0003] Aluminum-silicon alloy is one of the most widely used alloys in cast aluminum alloys. In order to improve its mechanical properties, the following methods are currently adopted. First, the alloy properties are enhanced by adding a second phase. In aluminum-silicon alloys, a small amount of magnesium is usually added to form Mg2Si phase after heat treatment. However, due to the relatively small amount of Mg2Si phase, its improvement on mechanical properties is limited. In addition, although the addition of micron reinforcement phase to aluminum-silicon alloy can improve its tensile strength and yield strength, this often leads to a significant decrease in toughness and plasticity, and there are problems such as difficult machining and uneven distribution of reinforcement phases, which have severely restricted the application of aluminum-silicon alloys. Another method is to refine the solidification structure. Rapid cooling technology has been widely used in the solidification process, and selective laser melting technology, with its characteristics of rapid solidification and rapid cooling, makes the prepared alloy usually have a uniform and fine grain structure. For aluminum-silicon alloys, refining the solidification structure is the key to obtaining high-performance aluminum alloys. However, due to the characteristics of high thermal conductivity and high temperature of aluminum-silicon alloy melts, how to more effectively refine its structure during solidification has always been a challenge.
[0004] During the solidification process, nanoparticles can not only effectively refine the solidification structure of aluminum-silicon alloys, but also play the role of second phase strengthening. Compared with the micron-reinforced phase, the nano-reinforced phase can greatly improve the mechanical strength of aluminum-silicon alloys while maintaining good toughness. Due to the excellent mechanical properties, electrical conductivity and thermophysical properties of the nano-reinforced phase, it has great potential in strengthening aluminum alloys. In aluminum-silicon alloys strengthened by nano-reinforced phases, the nano-reinforced phase can not only affect the size and morphology of the silicon phase, but also further improve the performance of the aluminum-silicon alloy.
[0005] In the field of metal material preparation, the selective laser melting additive manufacturing process is known for its extremely high solidification and cooling rates, which makes the alloy grains relatively small. In order to further improve the material performance, a common method is to add a variety of alloy elements to the alloy melt. Taking aluminum silicon alloy as an example, the commonly used treatment methods are to refine the primary α-Al phase, optimize the refinement and modification of eutectic silicon, and refine the primary silicon. The application of nanoparticle reinforcement phase is particularly prominent in material strengthening. They can not only promote the refinement of silicon phase (including primary silicon and eutectic silicon) in aluminum silicon alloy, but also refine the primary α-Al phase. At the same time, nanoparticles can also play a role in second phase strengthening, thereby significantly improving the strength of aluminum silicon alloy. The addition of nanoparticles can also significantly improve the plasticity and toughness of aluminum silicon alloy. In addition, the mechanism of nanoparticle refinement of primary α-Al phase is that they can form a nanoparticle layer on the surface of primary α-Al. This structure effectively hinders the growth of primary α-Al, thereby achieving grain refinement. This refinement effect helps improve the overall performance of aluminum silicon alloys, making them more competitive in many applications. Summary of the invention
[0006] The purpose of the present invention is to provide an additive manufacturing method for generating nanoparticle reinforcement phase by in-situ reaction of aluminum silicon alloy. The general method usually adopts an external addition method to obtain the reinforcement phase, that is, the reinforcement phase is mixed with the matrix alloy powder in advance, mechanically mixed or ball milled, and then pressed and sintered into a new material by hot pressing. The reinforcement phase obtained by this method is often coarse and unevenly distributed; the present invention proposes a method for introducing a reaction gas during the laser additive manufacturing process to generate a variety of reinforcement phase particles in the metal matrix, thereby improving the deformation resistance of aluminum silicon alloy manufactured by selective laser melting additive forming and further strengthening the quality of the alloy.
[0007] The purpose of the present invention can be achieved by the following technical scheme: an additive manufacturing method for generating nanoparticle reinforcement phase by in-situ reaction of aluminum-silicon alloy, characterized in that a certain volume fraction of reaction gas is introduced during the alloy selective laser melting additive forming process, and the reaction gas reacts with the liquid metal alloy element under the action of the laser beam to realize the in-situ production of the nanoparticle reinforcement phase inside the material.
[0008] Furthermore, the specific steps of the additive manufacturing method are:
[0009] Step S1, digital model preparation and pre-printing preparation; determine the placement position and angle of the part selection area laser melting additive forming, slice the modeled part 3D model and plan the forming path through the software, and select the laser power, scanning speed and laser scanning strategy;
[0010] Step S2, substrate and powder preparation; wipe the substrate clean before the experiment, dry the metal powder, load it into the forming chamber according to the equipment requirements after cooling, and set the powder layer thickness; load the metal powder into the spare powder pool;
[0011] Step S3, preparing a mixed protective gas; mixing the reaction gas in a certain proportion and then connecting it to the selective laser melting additive forming equipment, wherein the volume fraction of the reaction gas is greater than 50%, and the gas flow rate and connection pressure are set according to the gas mixing ratio;
[0012] Step S4, selective laser melting additive forming of the part; the additive forming of the part is completed according to the normal selective laser melting equipment operation steps; during the process, the inert atmosphere protective gas changes its composition in three stages, and after the forming is completed, the part to be formed and the substrate are cooled, and then the formed part and the substrate are taken out.
[0013] Furthermore, in step S3, the reaction gas is high-purity N2, C2H2 or N2, C2H2 with a volume fraction higher than 50%, and the purity of the N2, C2H2 reaction gas used is 99.99%.
[0014] Furthermore, in step S3, the reaction gas is a mixed gas of high-purity argon gas, and the purity of the high-purity nitrogen gas used is 99.99%.
[0015] Furthermore, in step S4, the composition of the inert atmosphere protective gas is changed in three stages, specifically: high-purity argon gas before the additive forming of the part begins, the reaction gas is used after the additive forming of the part begins, and high-purity argon gas is used in the cooling stage after the additive forming of the part is completed.
[0016] The beneficial effects of the present invention are:
[0017] (1) The present invention proposes a method for introducing reaction gases such as N2 and C2H2 during the selective laser melting additive forming process to produce a variety of reinforcing phase particles in the aluminum silicon alloy matrix, thereby improving the metal properties. The method is based on the in-situ autogenous method to obtain the reinforcing phase. Through chemical reactions between elements or between elements and compounds, chemical reactions occur between the molten pool formed by laser melting powder and the gas, and nano-reinforced phases are continuously generated at the interface. The intense convection of the molten pool under the action of the laser is used to achieve uniform distribution of the particle phase inside the material. The advantages of this process are that the required equipment and environmental conditions are simple, suitable for mass production, and the distribution uniformity of the reinforcing phase in the matrix is good.
[0018] (2) The nano-reinforced phase generated in situ in the present invention is fine, avoiding the generation of coarse secondary phases, and the nano-reinforced phase is evenly distributed. The present invention adds a large amount of nano-sized reinforcing phase to the selective laser melting additive manufacturing metal material, reduces the grain size, and provides a second phase strengthening effect, thereby improving the density and mechanical properties of the formed parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention will be further described below in conjunction with the accompanying drawings:
[0020] Figure 1 It is the microstructure and morphology characteristics of the AlSi10Mg aluminum alloy part selected laser melting additive forming specimen prepared by taking the parameters in the example in a mixed atmosphere of high-purity nitrogen and high-purity acetylene. DETAILED DESCRIPTION
[0021] The inventor of the present invention has concluded through a large amount of theoretical research and experimental verification that in the laser melting additive forming process of aluminum-silicon alloy, the gas-liquid reaction between N2, C2H2 and other reaction gases and the molten pool liquid metal can generate nano-enhanced phases. The reaction gases such as N2 and C2H2 are introduced into the environmental protection gas of the laser melting additive forming of aluminum-silicon alloy, and the reaction between N and Mg is used to generate Mg3N2, and then Mg3N2 reacts with aluminum to generate nano-scale AlN phase; while C2H2 gas reacts with Si element at high temperature to generate SiC nano-nanoparticles.
[0022] The first step is to prepare the digital model and the printing process. Determine the placement and angle of the laser melting additive forming of the part selection area, slice the built 3D model of the part through the software, plan the forming path, and select the process parameters such as laser power, scanning speed and laser scanning strategy.
[0023] The third step is substrate and powder preparation. The substrate and powder are dried before the experiment, and after cooling, they are loaded into the forming chamber according to the equipment requirements, and the powder layer thickness is set; the metal powder is loaded into the powder bin.
[0024] The fourth step is to prepare the mixed protective gas. Mix high-purity N2 gas and high-purity C2H2 gas in a certain proportion and then connect them to the selective laser melting additive manufacturing equipment, and set the gas flow rate and connection pressure.
[0025] The fifth step is the selective laser melting additive forming of the parts. The additive forming of the parts is completed according to the normal selective laser melting equipment operation steps; during this period, the inert atmosphere protection gas is divided into three stages, namely high-purity argon, a mixture of high-purity argon and reactive gas, and high-purity argon. After the forming is completed, the part to be formed and the substrate are cooled and the formed part is taken out.
[0026] The composition of the atmosphere used is changed in stages, specifically: high-purity argon before forming begins, a mixed gas of high-purity argon and reaction gas after forming begins, and high-purity argon in the cooling stage at the end of forming.
[0027] Among them, the reaction gas introduced is pure N2, C2H2 and other reaction gases or a mixed gas of N2, C2H2 and other reaction gases with a volume fraction higher than 50% and high-purity argon; the purity of the high-purity nitrogen used is 99.99%, and the purity of the N2, C2H2 and other reaction gases used is 99.99%.
[0028] This example specifically includes the following steps:
[0029] The first step is digital model preparation and pre-printing preparation. Create a 10mm×10mm×10mm square sample model and a 80mm×10mm×3mm sheet tensile sample, place the parts in the middle of the substrate without adding support; slice and plan the forming path of the built three-dimensional model of the parts through software, with a layer thickness of 0.03mm, and use a single raster square scanning path to fill, with an inter-layer rotation of 67°, and set the laser power to 230W and the scanning speed to 1300mm / s.
[0030] The second step is substrate and powder preparation. The aluminum alloy substrate and AlSi10Mg aluminum alloy powder with a particle size of 15μm-60μm are placed in a vacuum drying oven for drying to remove water vapor in the powder. The drying time is 4 hours, the drying temperature is 120℃, and the vacuum degree is better than 10Pa. The powder layer thickness is set to 0.03mm, and the metal powder is loaded into the powder bin.
[0031] The third step is gas preparation. Connect argon gas, and when the oxygen content of the atmosphere is lower than 100ppm, connect the mixed 80% N2+20% C2H2 to the selective laser melting additive forming equipment, and set the gas flow rate and connection pressure.
[0032] The fourth step is the selective laser melting additive forming of the part. The additive forming of the part is completed according to the normal selective laser melting equipment operation steps.
[0033] The fifth step is to stop the laser output after the forming is completed, enter the part cooling stage, change the inert atmosphere protective gas to high-purity argon, wait for the formed parts and substrate to cool down, and then take out the formed parts.
[0034] After the above forming is completed, the formed test block is taken out for organization observation and performance testing.
[0035] The alloy structure prepared by the method of the present invention was observed, and the results are as follows: Figure 1 As shown. Figure 1It can be observed that the AlSi10Mg alloy prepared in nitrogen and acetylene atmosphere contains a large number of nano-sized particles, which are evenly distributed and have no obvious coarsening behavior. This shows that the particles generated in situ by gas-liquid reaction have good thermal stability.
[0036] Table 1 Measurement data of tensile properties of AlSi10Mg aluminum alloy formed by selective laser melting additive manufacturing
[0037]
[0038] The tensile properties of the AlSi10Mg alloy formed by selective laser melting were tested, and the average value of the three measurements was taken, and the results are shown in Table 1. From the test results, it can be seen that the tensile strength of the AlSi10Mg alloy prepared in nitrogen and acetylene atmospheres is significantly improved due to the presence of a large number of nanoparticles.
Claims
1. An additive manufacturing method for generating a nanoparticle reinforcement phase by in-situ reaction of aluminum-silicon alloy, characterized in that: During the alloy selective laser melting additive forming process, a certain volume fraction of reaction gas is introduced. Under the action of the laser beam, the reaction gas reacts with the liquid metal alloy elements to realize the original production of nanoparticle reinforcement phase inside the material.
2. The additive manufacturing method for generating nanoparticle reinforcement phase by in-situ reaction of aluminum-silicon alloy according to claim 2, characterized in that: The specific steps of the additive manufacturing method are: Step S1, digital model preparation and pre-printing preparation; determine the placement position and angle of the part selection area laser melting additive forming, slice the modeled part 3D model and plan the forming path through the software, and select the laser power, scanning speed and laser scanning strategy; Step S2, substrate and powder preparation; wipe the substrate clean before the experiment, dry the metal powder, load it into the forming chamber according to the equipment requirements after cooling, and set the powder layer thickness; load the metal powder into the spare powder pool; Step S3, preparing a mixed protective gas; mixing the reaction gas in a certain proportion and then connecting it to the selective laser melting additive forming equipment, wherein the volume fraction of the reaction gas is greater than 50%, and the gas flow rate and connection pressure are set according to the gas mixing ratio; Step S4, selective laser melting additive forming of the part; Follow the normal selective laser melting equipment operating steps to complete the additive forming of the part; During the forming process, the inert atmosphere protective gas changes its composition in three stages. After the forming is completed, the formed parts and the substrate are cooled and then taken out.
3. The additive manufacturing method for generating nanoparticle reinforcement phase by in-situ reaction of aluminum-silicon alloy according to claim 2, characterized in that: In step S3, the reaction gas is high-purity N2, C2H2 or N2, C2H2 with a volume fraction higher than 50%, and the purity of the N2, C2H2 reaction gas used is 99.99%.
4. The additive manufacturing method for generating nanoparticle reinforcement phase by in-situ reaction of aluminum-silicon alloy according to claim 3, characterized in that: In step S3, the reaction gas is a mixed gas of high-purity argon gas, and the purity of the high-purity nitrogen gas used is 99.99%.
5. The additive manufacturing method for generating nanoparticle reinforcement phase by in-situ reaction of aluminum-silicon alloy according to claim 3, characterized in that: In step S4, the composition of the inert atmosphere protective gas is changed in three stages, specifically: high-purity argon gas before the additive forming of the part begins, the reaction gas is used after the additive forming of the part begins, and high-purity argon gas is used in the cooling stage after the additive forming of the part is completed.
Citation Information
Cited By
Heat-resistant aluminum-based composite material and selective laser melting forming preparation method and application thereof
CN120680010A
In-situ conversion porous component based on selective laser melting and manufacturing method thereof
CN121156299A